2018
DOI: 10.1063/1.5008371
|View full text |Cite
|
Sign up to set email alerts
|

Extension of local front reconstruction method with controlled coalescence model

Abstract: The physics of droplet collisions involves a wide range of length scales. This poses a challenge to accurately simulate such flows with standard fixed grid methods due to their inability to resolve all relevant scales with an affordable number of computational grid cells. A solution is to couple a fixed grid method with subgrid models that account for microscale effects. In this paper, we improved and extended the Local Front Reconstruction Method (LFRM) with a film drainage model of Zang and Law [Phys. Fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…It can be concluded that the Diffuse Interface Model gives detailed insight into droplet collision dynamics, which leads to a better understanding of the process. The results of simulations of droplet collisions with DIM can be used to either validate or improve coalescence models employed in sharp interface methods [18,31]. It must be noted, however, that the temperature range in which DIM can be used is severely limited by a constraint on the grid spacing caused by the fact that the liquid-vapor interface becomes very thin when the temperature is far from the critical point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the Diffuse Interface Model gives detailed insight into droplet collision dynamics, which leads to a better understanding of the process. The results of simulations of droplet collisions with DIM can be used to either validate or improve coalescence models employed in sharp interface methods [18,31]. It must be noted, however, that the temperature range in which DIM can be used is severely limited by a constraint on the grid spacing caused by the fact that the liquid-vapor interface becomes very thin when the temperature is far from the critical point.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that when other multiphase simulation methods are used to simulate droplet collisions, the total amount of energy is not guaranteed to be conserved. A decrease in the total amount of energy is observed during the collision process in the following studies: Nobari et al [24], Rieber and Frohn [33], Sun et al [41] and Rajkotwala et al [31]. The loss in total energy can be as high as 20% and is usually caused by an equivalent loss in interfacial energy due to a sudden reduction of interfacial area.…”
Section: Energy Transfer and Dissipationmentioning
confidence: 96%
See 1 more Smart Citation
“…The numerical model used in the present work is based on the LFRM, originally developed by Shin et al (2011) and extended by Mirsandi et al (2018) and Rajkotwala et al (2018). The main characteristics of the numerical model are described in the section below.…”
Section: Methodsmentioning
confidence: 99%
“…A time series showing a head-on separation of two colliding drops can be appreciated in Fig. 18 (the first two panels are obtained from numerical simulations [231,261], while the third from experimental measurements [260]). For intermediate values of the impact parameter, the smaller normal component of the impingement inertia reduces the internal flow responsible for the separation [260] and permanent coalescence is obtained (regime III, coalescence with high deformation).…”
Section: Drop Size Distribution and Advancementsmentioning
confidence: 99%